The hegemony behind "Freedom to study on an independent campus (MBKM)": A Gramsci analysis - Juniarsih Nur , Rezky; Aba, Akbar; Nur, Jumiati (Jurnal Edukasi Terkini, 2024)
The MBKM curriculum is a representation of educational changes based on industrial growth 4.0. The hegemony related to MBKM is increasingly being promoted by the government and almost all universities are implementing the MBKM curriculum. However, in Gramsci's view, there has been criticism that needs to be studied, especially regarding the MBKM Certified Internship program in a company or industry. The global tendency to emphasize skills And arrangement output has requires transformation draft deep base curriculum in all over world, start from teaching, knowledge, And Education new curriculum' is not a linear process of increasing homogenization but develops in surprising directions. This research uses qualitative methodology. This form of research is classified as library research in accordance with the research objectives, first by documenting all results related to the implementation of the Campus Independent Learning (MBKM) policy. Review MBKM through draft "hegemony" Gramsci. Hegemony happen when the proletariat And they Which is at in lower Already adopt And copy style life, philosophy, and the worldview of the elite group that controls and exploits them. According to Gramsci, hegemony will give birth to submission, a mindset that accepts conditions without examining them critically. This is because the ideology exposed by the hegemonic class is only digested in its raw form. A class group is considered hegemonic when it succeeds in establishing and maintaining alliances with other social and class forces through ideological and political conflict. So Gramsci saw that MBKM and overhauling the education system were hegemonic goals for survival capitalism.